Design and Implementation of Robofly Wing Flapping Mechanism Using Piezoelectric Crystal - Mohamed Fuad Al Farabi Shazi B Shaarani, Mohamed Fuad Al Farabi Shazi (Universiti Teknologi Petronas, 2008)
Micromechanical Flying Insect (MFI) or simply ‘robofly’ is a newly introduced air vehicle which is tiny and maneuverable. It is a project requiring collaboration from several academic areas such as biology, robotics and engineering. The target robotic insects are electromechanical devices propelled by a pair of independent flapping wings to achieve sustained autonomous flight, thereby mimicking real insects. Part of the research involves trying to figure out how insects, and specifically flies, flap their wings with high speed and intensity. Initiation stage of this project was to conduct thorough study and research on the robofly. Considering high frequency of flapping motion, robofly is best actuated by piezoelectric ceramics. The direct piezoelectric effect is that piezo ceramic generates an electrical charge during mechanical distortion or load. During an inverse piezoelectric effect the piezoceramic body changes under the influence of an electrical field. The Piezoelectric effect can occur under the influence of external forces. Depending on the force direction electrical charges with corresponding polarity are generated. An inverse piezoelectric effect takes place under the influence of electrical fields. The body changes its dimension along with the change of voltage. The main objective of this project is mainly the design of the thorax structure for robofly and it is defined as the most critical part during this project ongoing. The most efficient method for the robofly to take off into the air is to design a flapping mechanism actuated by piezoelectric. Using a four bar linkage, small piezoelectric linear displacement can be converted to rotational wing motion at high frequency. Solid model design and motion simulation has been generated for both options. The output from both designs are to be compared and the best output in terms of wing stroke angle being picked as best design.